TINJAUAN YURIDIS KERINGANAN ANSURAN DALAM KEWAJIBAN MEMBAYAR HUTANG SEBAGAI AKIBAT KEADAAN MEMAKSA KARENA COVID-19 Di INDONESIA - Denop Yohannes Tampubolon, (2021)
This study was conducted to find out how the legal consequences that arise by doing installment relief in the obligation to pay debts in the event that the debtor does not pay the installments as a result of forced circumstances and what efforts are taken by the parties, both creditors and debtors in carrying out their obligations to pay debts as a result of forced circumstances. because of COVID-19 in Indonesia? This type of research is normative juridical, with a statutory approach, the data comes from secondary data. The results obtained in this paper are that circumstances of coercion cannot directly be a reason to cancel the agreement. It is necessary to ensure beforehand that in the agreement there is a coercive condition clause determined by the parties. Forced circumstances have the nature of postponing obligations, which can also be interpreted to eliminate the obligation to pay losses and interest, not to eliminate the debtor's obligations completely. Debtors can restructure if they experience difficulties in payment, this is regulated in the Peraturan Otoritas Jasa Keuangan Number 11/POJK.03.2020 of 2020. POJK.